Pilot Study on the Responsiveness of Nurses to the Patient’s Request for complementary medicine (Journal of Health Sciences, 2017)
Introduction: When it comes to integrative medicine, the nurses are "caught in a trap" of their own views and developed competencies, as well as the views of the institution and the country where they work. The pilot study’s objective was to explore what is the expected reaction of nurses to the patient’s request for complementary treatment with tea in hospitals where integrative nursing has not yet been normatively recognised.Methods: The quantitative research approach with a survey was used. Nonprobability sampling covered 506 persons from Southeast Slovenia, paticipating voluntarily: nurses, nursing students, patients and other persons. Respondents were to choose among the 11 previously prepared scenarios of possible responses of the nurse.Results: Significant differences regarding the expected reaction of nurses both within the groups, as well as between the groups of respondents were found. The most possible critical response of nurses was to offer the tea which is daily available on the ward. A fifth of respondents believe that the patient’s tea would be provided by the visiting relatives.Conclusion: Due to the prepared scenarios, findings and given orientations for further research, the study can be further implemented in the international environment for empirical verification.